Tissue Volume and Section Area Changes of Paraffin and Methacrylate Embedded Testicular Sections: An Unbiased Design Study - Yang Guo; Yu Xiang; Dan Wang; Zheng-Wei Yang (Image Analysis and Stereology)
For stereological estimates of structures in an organ such as total number (particles), length or surface area, the tissue change after processing (usually embedding of tissue blocks, sectioning of embedded blocks, and mounting and staining of sections) may need to be estimated to correct the results obtained on final sections so as to reflect the true results in the organ before processing. We proposed that the correction be made depending on the stereological principle used: correction for estimation with 3-dimensional and 2-dimensional measurements be based on different tissue volume and section area changes. Previous researches on tissue changes were limited and overlooked different corrections. Using paraffin and methacrylate embedded testicular sections, we studied, with an unbiased design, the tissue volume and section area changes after processing. The results demonstrated that the overall change of the actual tissue volume of paraffin sections was a marked shrinkage of 21%-23% while that of methacrylate sections was a small expansion almost negligible; compared with area of the embedded block face, the final section area had a 4% decrease in paraffin but an 8% increase in methacrylate. The results were tentatively used for correction of estimates in some of previous studies. The present study provides both methods and data for experiments involving the study of tissue change for better stereological estimation.